Addressing the challenges towards the adoption of digital technologies in construction supply chain management - Uzor Onyia; Izuchukwu Stanley Ani; Uchechukwu Frank Nwankwo (Discover Civil Engineering)
Abstract Supply chain management has shown to be an aspect of construction that is neglected, yet with great impact on project delivery time frames and the overall cost of construction projects. This research seeks to identify, assess, and propose solutions for the challenges hindering the adoption of digital technologies in construction supply chain management, hence creating a sustainable foundation for practitioners and relevant agencies to leverage the benefits of digital technologies in the management of construction supply chain. The literature review identified challenges of digital technology adoption in construction supply chain management, guiding subsequent research. A structured questionnaire captured demographic data and insights, with 171 industry professionals surveyed. Data analysis, including Likert scale ratings and Relative Impact/Feasibility Index, informed an Impact-Feasibility Matrix. This matrix categorized challenges and strategies into quadrants, aiding prioritization. A conceptual framework emerged, offering actionable insights for addressing adoption challenges. The study identified 14 challenges to digital technology adoption in construction supply chain management, ranked by respondents. These challenges were categorized based on their impact and feasibility, with strategies mapped accordingly. The resulting framework prioritizes High Impact/High Feasibility challenges for action, while Low Impact/Low Feasibility challenges may require further exploration. This strategic approach aims to address key hurdles efficiently, enhancing the adoption of digital technologies in construction supply management. The findings from this study will inform construction practitioners and relevant agencies about the challenges hindering the seamless integration of digital technologies into construction supply chain management and propose feasible strategies for addressing these challenges.